Imaginative geographies in the present time: from the Third World to the Global South (Tempo e Argumento, 2024)
This article presents a historical interpretation of the political perceptions associated with the notion of Global South, in which Brazilian society has been situated in the present time. To this end, it takes “Global South” as an imaginative geography in dispute, which both mediates encounters, confrontations and international connections and influences the contours of political relations in countries such as Brazil. Between a political representation marked by the so-called third worldism and the new transnational configuration, hegemonized by neoliberalism, from the 1970s onwards, social conflicts and political projects in Brazilian society were redimensioned, amidst a contradictory process of democratization and limited exercise of human rights.
Keywords: Global South; Third World; imaginative geography; politics; democracy